2020
DOI: 10.1136/gutjnl-2019-319804
|View full text |Cite
|
Sign up to set email alerts
|

Substantial and sustained improvement of serrated polyp detection after a simple educational intervention: results from a prospective controlled trial

Abstract: ObjectiveSerrated polyps (SPs) are an important cause of postcolonoscopy colorectal cancers (PCCRCs), which is likely the result of suboptimal SP detection during colonoscopy. We assessed the long-term effect of a simple educational intervention focusing on optimising SP detection.DesignAn educational intervention, consisting of two 45 min training sessions (held 3 years apart) on serrated polyp detection, was given to endoscopists from 9 Dutch hospitals. Hundred randomly selected and untrained endoscopists fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…However, ADR also increased at the control sites (from 36% to 39%); therefore, there was only limited evidence of a training effect. 34 A randomised trial from Dutch hospitals showed that two 45 min training sessions improved the detection rate for SSPs from 9.3% to 15.6% 35 A meta-analysis of 12 intervention studies (1 randomised controlled trial (RCT) and 11 non-RCTs involving 154 endoscopists and 33 184 colonoscopies) compared ADR prefeedback and postfeedback interventions. 36 The pooled ADR at baseline was 30.5% and 36% after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, ADR also increased at the control sites (from 36% to 39%); therefore, there was only limited evidence of a training effect. 34 A randomised trial from Dutch hospitals showed that two 45 min training sessions improved the detection rate for SSPs from 9.3% to 15.6% 35 A meta-analysis of 12 intervention studies (1 randomised controlled trial (RCT) and 11 non-RCTs involving 154 endoscopists and 33 184 colonoscopies) compared ADR prefeedback and postfeedback interventions. 36 The pooled ADR at baseline was 30.5% and 36% after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…32 Increased awareness of the clinical importance of SSA/P through educational training had also been shown to improve SSA/PDR. 33 ADR and AADR are positively correlated with SSA/PDR. 7,8 However, unlike ADR, existing knowledge on SSA/P and their detection are considerably limited, which makes our report clinically relevant.…”
Section: Discussionmentioning
confidence: 87%
“…As the second point, we evaluated the CSSDR as well as the ADR and showed that just feedback without training made CSSDR rise. Bleijenberg et al 16 reported educational interventions improved proximal SP detection rate. However, our study indicated that just feedback might be enough.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared data before and after feedback in a short period. The long-term effect of the feedback is controversial 12 16 . Additionally, we did not clarify whether the simple feedback given only once or just the fact of being continuously observed after the feedback improved the studied outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation